Lead-based paint remains a major public health concern: A critical review of global production, trade, use, exposure, health risk, and implications - O'Connor, David; Hou, Deyi; Ye, Jing; Zhang, Yunhui; Sik Ok, Yong; Song, Yinan; Coulon, Frederic; Peng, Tianyue; Tian, Li (Elsevier, 2018)
Human exposure to lead (Pb) is a growing global public health concern. Elevated blood lead is thought to cause the mental retardation of >0.6 million children globally each year, and has recently been attributed to ~18% of all-cause mortality in the US. Due to the severe health risk, the international community, led by the United Nations Environment Programme (UNEP) and the World Health Organization (WHO), is actively supporting the global phase-out of lead-based paint by 2020. However, there are many significant hurdles on the way to achieving this goal. In light of the importance of the lead-based paint issue, and the urgency of achieving the 2020 phase-out goal, this review provides critical insights from the existing scientific literature on lead-based paint, and offers a comprehensive perspective on the overall issue. The global production and international trade of lead-based paints across Asia, Africa, Latin America, and Europe are critically discussed – revealing that lead-based paints are still widely used in many low and middle-income developing countries, and that the production and trade of lead-based paint is still wide-spread globally. In India, as well as many south-east Asian, African, Latin American and European countries, lead concentrations in paints often exceed 10,000 mg/kg. This will certainly pose a serious global threat to public health from surfaces painted with these products for many decades to come. The sources and pathways of exposure are further described to shed light on the associated health risk and socioeconomic costs. Finally, the review offers an overview of the potential intervention and abatement strategies for lead-based paints. In particular, it was found that there is a general lack of consensus on the definition of lead based paint; and, strengthening regulatory oversight, public awareness, and industry acceptance are vital in combating the global issue of lead based paint.
Keywords: Lead-based paint; Lead exposure; Blood lead level; Soil contamination